Does audit quality moderate the impact of environmental, social and governance disclosure on firm value? Further evidence from Egypt - Mohamed Samy El-Deeb; Tariq H. Ismail; Alia Adel El Banna (Journal of Humanities and Applied Social Sciences, 2023)
Purpose – This paper aims to examine the impact of environmental, social and governance (ESG) disclosure and firm value (FV), as well as, pinpoints the role of the audit quality (AQ) as a moderating variable on such impact; where the authors hypothesize that AQ modulates the relationship between ESG disclosure and the FV. Design/methodology/approach – Data of a sample of firms listed on the Egyptian Stock Exchange Market (EGX) were collected over the period of 2017–2021 and analyzed using the regression and 2SLS models. Findings – The results suggested that: (1) the ESG has a significant positive impact on the FV in the EGX, and (2) AQ has a significant impact, as a moderating variable, on the relationship between ESG disclosure and FV. Research limitations/implications – The findings would help the Egyptian market authorities in realizing the importance of integrating ESG information within the financial reports of the listed firms. The findings could also help in developing effective disclosure procedures to provide shareholders with useful information. Originality/value – This paper contributes to the literature regarding the ESG disclosure components and the FV value by considering AQ in testing such relationship.